Implementasi Promosi Kesehatan Rumah Sakit Umum Daerah Haji Kota Makassar - Rahmawati; Harpiana Rahman; Ayu Puspitasari (Window of Public Health Journal, 2025)
Through Hospital Health Promotion (PKRS), implementers can develop the understanding and knowledge of healthy visitors, as well as patients and their families, regarding the prevention and treatment of diseases. Health promotion media encompass all means or efforts to convey messages or information that the communicator intends to convey. The purpose of this study is to describe the image of health promotion media at the Haji Makassar Regional General Hospital. The type of research employed in this study is qualitative, with a descriptive approach. Informants in this study were the PKRS team and hospital visitors. Data collection techniques used observation, interview, and documentation guidelines. From the study's results, planning for media production was conducted, including determining the material, implementing the media used in the hospital, and evaluating the success of media implementation. This process enabled the description of health promotion media at the Haji Makassar Regional General Hospital. It is hoped that future researchers will examine other variables to demonstrate how the media portrays hospitals.